Preparing students for the future workforce: An experiential learning approach to deliver an accounting analytics course - PAN, Gary (Institutional Knowledge at Singapore Management University, 2016)
This paper describes an undergraduate accounting analytics course which was delivered based on an experiential learning approach. This accounting analytics course is timely as, with the proliferation of Big Data, several accounting professional bodies have highlighted the importance of developing analytical skills among accounting graduates. The experiential learning approach was adopted because there is a need to equip students with future work skills so as to tackle increasingly complex problems. The professors collaborate with external partners to design a course which combines theory with experiential learning through heavy use of projects involving real world problems. Students rated the course favourably. The students’ feedback indicated that the experiential learning approach is beneficial for their overall learning outcomes such as enhancing their problem-solving, analytical, reasoning and communication skills. The course demonstrates a curriculum design that integrates industry experience with classroom learning. External partners were also supportive of the experiential learning approach.